Dual-incision minimally invasive fasciotomy of the anterior and peroneal compartments for chronic exertional compartment syndrome of the lower leg - Grechenig, Christoph (Sci Rep, 2020)
To evaluate the risk of iatrogenic injury when using a dual-incision minimally invasive technique to decompress the anterior and peroneal compartments of the lower leg. Forty lower extremities from 20 adult cadavers, embalmed with Thiel’s method, were subject to fasciotomy of the anterior and peroneal compartment using a dual-incision minimally invasive fasciotomy. The first incision was made 12 cm proximal to the lateral malleolus to identify and protect the superficial peroneal nerve (SPN). The second incision was made at the mid-point of the Fibula (half-way between the fibular head and the lateral malleolus). Release of the anterior and peroneal compartments was successful in all specimens. Two nerve injuries of the superficial peroneal nerve were reported. More precisely, in these cases the medial dorsal cutaneous nerve got injured during the fascial opening of the extensor compartment. Two incision minimally invasive fasciotomy to decompress the anterior and peroneal compartments of the lower leg appears to be safe with regard to the results of this study.